2001
DOI: 10.1111/j.1574-0862.2001.tb00215.x
|View full text |Cite
|
Sign up to set email alerts
|

A fresh meat almost ideal demand system incorporating negative TV press and advertising impact

Abstract: This paper investigates fresh meat consumption in Belgium during 1995-1998 through the specification of a three-equation almost ideal demand system (AIDS) incorporating a media index of TV coverage and advertising expenditures as explanatory variables. Estimated parameters and elasticity coefficients are plausible and consistent with demand theory. Own-price elasticities are relatively low, indicating a low fresh meat demand sensitivity to price changes over this period which was dominated by mass media report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…Their results indicate that the contemporaneous effects of health information are greater than the lagged effects, which indicates that the effect of information depletes rapidly and that advertising has a minor effect on demand. Verbeke and Ward [13] reported similar results.…”
Section: Theoretical Overviewsupporting
confidence: 77%
“…Their results indicate that the contemporaneous effects of health information are greater than the lagged effects, which indicates that the effect of information depletes rapidly and that advertising has a minor effect on demand. Verbeke and Ward [13] reported similar results.…”
Section: Theoretical Overviewsupporting
confidence: 77%
“…Animal-advocacy organisations are seen as more trustworthy sources of information than are animal industries (McKendree et al 2014), and this difference in credibility is magnified in the wake of animal-abuse exposés when attitudes towards the livestock sector are especially negative (Tiplady et al 2013). This may explain why negative press has a much greater impact on consumer behaviour than has any positive effect from advertising (Verbeke and Ward 2001).…”
Section: Educate the Publicmentioning
confidence: 93%
“…One study carried by Yang and Goddard (2011) found that consumer groups in Canada responded differently to a perceived BSE food safety issue. The aggregate beef consumption of BSE impacts in Canada was different than those in the United Kingdom, Germany, and Japan (Burton & Young, 1996;Verbeke & Ward, 2001;Mazzocchi, Lobb, Traill, & Cavicchi, 2008;Lim et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 88%